2017
DOI: 10.1590/1413-81232017229.11092017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à violência no ambiente de trabalho em agentes de segurança penitenciária do sexo feminino no Brasil

Abstract: Prevalência e fatores associados à violência no ambiente de trabalho em agentes de segurança penitenciária do sexo feminino no BrasilPrevalence and violence-associated factors in the work environment of female prison guards in Brazil (OR = 3,23; IC = 1,9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 18 publications
0
9
0
8
Order By: Relevance
“…Particularly in Brazil, violence was observed both between prisoners and officers, and prisoners with each other [23,50], which probably raises great concern among POs. The sustained level of violence inside prisons can make people apprehensive, particularly if these prisons fail to implement serious measures to prevent and manage violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in Brazil, violence was observed both between prisoners and officers, and prisoners with each other [23,50], which probably raises great concern among POs. The sustained level of violence inside prisons can make people apprehensive, particularly if these prisons fail to implement serious measures to prevent and manage violence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the occupancy rate of 171.62%, the prison population has been growing at a rate of approximately 6% per year [21]. Additionally, in Brazil as well as in other countries there are other aggravating conditions such as an increase in inmate members of organized crime, unsafe working conditions, and riots [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted among COs in several countries showed that the tension, stress, psychological/emotional suffering, night shifts, and work overload are factors that can explain how the prison environment influences the health of the group in question. 26,27 Generalized stress and stress in the workplace affect between 19% and 30% of employees in different sectors. 28 In prisons, this proportion grows, and about 41.2% of COs show signs of stress related to the type of work and environment in which they perform their duties.…”
Section: Discussionmentioning
confidence: 99%
“…A respeito do trabalho em equipe, Ferreira et al (2017) verificaram a prevalência e fatores associados à violência no ambiente de trabalho em ASP do sexo feminino no Brasil e constatou diversos aspectos que deterioram as boas relações entre os colegas de uma mesma equipe, colaborando para um aumento na tensão já pré-existente devido a função. Jaskowiak e Fontana (2015) reconhecem que mediante às condições precárias de trabalho e a rotina de suas atividades funcionais a saúde dos ASP fica exposta à riscos físicos e mentais.…”
Section: Concepção De Saúde Pelos Profissionaisunclassified